Dependence of the Ripeness Stage on the Antioxidant and Antimicrobial Properties of Walnut (Juglans Regia L.) Green Husk Extracts from Industrial By-Products - Gutierrez-Cutino, M; Gutierrez-Cutino, M; Matiacevich, S; Soto-Madrid, D (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Walnut green husk (WGH) is a waste generated by the walnut (Juglans regia L.) harvest industry. It represents a natural source of polyphenols, compounds with antioxidant and antimi-crobial activities, but their activity could be dependent on the ripeness stage of the raw material. In this study, the effect of the different ripeness stages—open (OH) and closed (CH) husks—on the antioxidant and antimicrobial properties of WGH extracts were analyzed, emphasizing the influence of the extracts in inhibiting Escherichia coli growth. The ripeness stage of WGH significantly affected the antioxidant activity of the extracts. This was attributed to the different polyphenol profiles related to the mechanical stress when the husk opened compared to the closed sample. The antimicrobial activity showed inhibition of E. coli growth. OH-extracts at 96 µg/mL caused the lowest specific growth rate (µmax = 0.003 h−1) and the greatest inhibition percentage (I = 93%) compared to CH-extract (µmax = 0.01 h−1; I = 69%). The obtained results showed the potential of the walnut green husk, principally open husk, as an economical source of antioxidant and antimicrobial agents with potential use in the food industry. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.